Hypoxanthine in the microenvironment can enable thiopurine resistance in acute lymphoblastic leukemia - Wang, Xiaohong; Ostergaard, Jason; Kang, Jongseok; Sagong, Grace; Twite, Rachel; Vargas-Morales, Andrea; Gordon, Peter M. (Frontiers in Oncology, 2024)
Acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy, with relapse being a major obstacle to successful treatment. Our understanding of the mechanisms driving chemotherapy resistance and ultimately relapse in leukemia remains incomplete. Herein, we investigate the impact of the tumor microenvironment on leukemia cell drug responses using human plasma-like media (HPLM), designed to mimic physiological conditions more accurately ex vivo. We demonstrate that while most chemotherapeutics maintain an efficacy in HPLM comparable to standard tissue culture media, the thiopurines 6-mercaptopurine (6-MP) and 6thioguanine (6-TG) exhibit significantly reduced potency and efficacy against both B-and Tleukemia cells in HPLM. By merging our understanding of thiopurines' mechanism of action with the metabolites supplemented in HPLM compared to standard media, we proposed and subsequently validated the hypothesis that hypoxanthine, a purine derivative, is responsible for conferring resistance to the thiopurines. Importantly, the concentration of hypoxanthine required for resistance is comparable to physiological levels found in vivo, supporting clinical relevance.Our findings demonstrate the utility of a more physiologic media in identifying and characterizing mechanisms by which the microenvironment can enable resistance. Understanding such interactions may inform strategies to overcome drug resistance and improve therapeutic outcomes in pediatric leukemia.